Akathisia Among Patients Undergoing Antipsychotic Therapy: Prevalence, Associated Factors, and Psychiatric Impact. Issue 4 (11th July 2022) - Jouini, Lamia; Ouali, Uta; Ouanes, Sami; Djebara, Mouna Ben; Nacef, Fethi; Gouider, Riadh
Abstract : Objectives: The prevalence of akathisia is variably reported in the literature and its psychiatric impact is little studied. The aim of this study was to establish the prevalence, the associated factors, and the psychiatric impact of akathisia among patients undergoing antipsychotic treatment. Methods: A cross-sectional descriptive study was carried out at the Department of Psychiatry A, at Razi Hospital, in Tunis. It included patients with psychosis, undergoing antipsychotic treatment, from June 2016 to February 2017. Akathisia was diagnosed according to the Barnes Akathisia Scale. Results: The prevalence of akathisia was 19.5% (n = 24, schizophrenia/schizoaffective disorder, n = 20; bipolar disorder, n = 4). The delay between the diagnosis of the disease and the onset of akathisia was 7.1 ± 8.8 years. Among the sample of patients with akathisia, 20/24 were on monotherapy of which 14 on conventional antipsychotics and six on atypical antipsychotics. Patients with akathisia were on atypical (8/24), low-potency conventional (4/24), or high-potency conventional (17/24) antipsychotics. The average dose of antipsychotics in chlorpromazine equivalent was 2294.5 ± 3037.7 mg. After adjusting for confounders, the only factor significantly positively associated with the diagnosis of akathisia was the dose of antipsychotics prescribed ( P = 0.01). The following psychiatric manifestations were reported by patients with akathisia: dysphoria/irritability (16/23), anxiety (18/24), sadness (15/24), suicidal thoughts (11/24), heteroaggressivity (8/23), sleep disturbances (16/24), and suicidal attempts (9/24). Conclusions: Despite the high psychiatric and social burden of akathisia, it remains largely underdiagnosed and undertreated, because in part of its subjective component.